Evidence-based Estimates of the Demand for Radiotherapy. Issue 2 (February 2015) - Delaney, G.P.; Barton, M.B.
Abstract There are different methods that may be used to estimate the future demand for radiotherapy services in a population ranging from expert opinion through to complex modelling techniques. This manuscript describes the use of evidence-based treatment guidelines to determine indications for radiotherapy. It also uses epidemiological data to estimate the proportion of the population who have attributes that suggest a benefit from radiotherapy in order to calculate the overall proportion of a population of new cases of cancer who appropriately could be recommended to undergo radiotherapy. Evidence-based methods are transparent and adaptable to different populations but require extensive information about the indications for radiotherapy and the proportion of cancer cases with those indications in the population. In 2003 this method produced an estimate that 52.4% of patients with a registered cancer-type had an indication for radiotherapy. The model was updated in 2012 because of changes in cancer incidence, stage distributions and indications for radiotherapy. The new estimate of the optimal radiotherapy utilisation rate was 48.3%. The decrease was due to changes in the relative frequency of cancer types and some changes in indications for radiotherapy. Actual rates of radiotherapy utilisation in most populations still fall well below this benchmark.